What the Greeks taught us and we British have forgotten. (July 2014) - Elcock, Howard James
The ancient Greek philosophers taught us many of the desirable features of government, but since 1979 we have lost sight of most of them. We now have a restricted view of citizenship, a defective view of the public interest, a diluted public service ethic, little public service education and training and above all we have lost sight of the Greeks' demand to seek the good life and the good society. Instead we have the 'Three Es' and a business approach which is profit led. Leadership and action are needed to restore the former virtues of British government, many of which were learnt from Plato and Aristotle.